Ecological risk analysis of heavy metals in farmland soil based on Monte Carlo simulation. Issue 1 (November 2020) - Zhu, Huina; Xing, Weiqin; Zhang, Liangbo; Zhang, Baozhong; Shi, Fan; Li, Liping; Chen, Hanyu
Abstract: This study is aimed to analyze ecological risk for heavy metals in farmland soil. In order to solve the problem of uncertainty in the risk assessment process, the potential ecological risk analysis based on Monte Carlo is established. The evaluation results showed that the probability of As belonging to low risk level was 100%; that of Pb belonging to low risk and medium risk were 34% and 66%; that of Cd belonging to extremely high risk and high risk were 97.44% and 2.56%. The risk of the three heavy metals was ranked as Cd > Pb > As. The probability of total risk belongs to extremely high risk and high risk was 99.48% and 0.52%. The method established in this study can reduce the error caused by a small sample. This study can put forward an objective evaluation methodology for the risk management of farmland pollution by heavy metals.